PENGARUH HARGA, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN OEMAH HERBORIST - Sasono, Eko; Sopi, Sopi; Nafiah, Zumrotun; Widiyasari, Dian (Solusi, 2023)
This study aims to determine the effect of price, product quality, and the company's brand image on customer satisfaction in Semarang Herborist Oemah. The sampling method in this study used purposive sampling, namely taking sample members based on certain criteria. The certain criteria used as samples are; 1). Consumers who buy products from Oemah Herborist are individual customers, not corporate customers (business customers). 2). Oemah Herborist Semarang consumers are those who buy Herborist products for the 2021 period. 3). Customers have purchased Herborist products at least 2 times. Based on the samples taken with certain criteria above, 100 people (respondents) were obtained. Hypothesis testing uses multiple linear analysis methods with SPSS tools. Price has a significant effect on consumer satisfaction with a t count > t table, namely 2.941 > 1.984 and a probability value of 0.004 <0.05, product quality has a significant effect on consumer satisfaction with a t count > t table, namely 3,331 > 1.984 and a probability value of 0.001 < 0.05 while brand image has no effect and is not significant on consumer satisfaction with a t count < t table, namely 1.101 < 1.984 and a probability value of 0.273 > 0.05. The suggestion in this study is that companies should pay attention to the pricing process and consider several price indicators so that prices will not be a problem for consumers. Companies must also maintain the quality of their products to maintain consumer satisfaction.